1988
DOI: 10.1113/jphysiol.1988.sp016972
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and water reabsorption in the proximal and distal nephron in conscious pregnant rats and third trimester women.

Abstract: SUMMARY1. Sodium and water reabsorption were determined in virgin controls and rats at 9 and 20 days of pregnancy during a water diuresis induced and maintained by infusion of 2f5% dextrose and in normally hydrated women during the third trimester and again 2-3 months after delivery.2. Reabsorption from the proximal tubules and distal nephron segments was assessed using the clearance of lithium as a marker of the sodium and water delivery from the proximal tubules to the loops of Henle.3. Glomerular filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 34 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, plasma volume expansion found during pregnancy is associated with a rise in the glomerular filtration rate in the rat (Baylis, 1987), which in turn increases Na + filtration and reabsorption rates. Increases in Na + reabsorption are observed during gestation in both proximal tubules and distal nephrons of the rat kidney (Atherton et al 1988). In view of the above, the decrease we found in plasma urea concentration in the pregnant rats on the normal diet may be due to both extracellular fluid expansion and the decrease in P osm .…”
Section: Renal Function Osmoregulation and Angii Receptor Expressionmentioning
confidence: 50%
“…Furthermore, plasma volume expansion found during pregnancy is associated with a rise in the glomerular filtration rate in the rat (Baylis, 1987), which in turn increases Na + filtration and reabsorption rates. Increases in Na + reabsorption are observed during gestation in both proximal tubules and distal nephrons of the rat kidney (Atherton et al 1988). In view of the above, the decrease we found in plasma urea concentration in the pregnant rats on the normal diet may be due to both extracellular fluid expansion and the decrease in P osm .…”
Section: Renal Function Osmoregulation and Angii Receptor Expressionmentioning
confidence: 50%
“…Therefore, aldosterone may play a more important role in sodium homeostasis, whereas deoxycorticosterone may play a more integral role in promoting sodium retention. Finally, considering the remarkable GFR-mediated increment in sodium filtration, glomerulotubular changes are needed to ensure sodium reabsorption in the proximal and distal tubules to avoid excessive renal solute losses (70). Some authors have suggested that this may be mediated by increments in the number of renal Na1/K1 ATPase (71), but this is controversial (72).…”
Section: Electrolyte Balancementioning
confidence: 99%
“…Lithium clearance studies in women have indicated enhanced sodium reabsorption in the proximal tubule and distal nephron segments in late pregnancy, whereas animal studies have been contradictory. 36 The reason for the net renal sodium retention in pregnancy is not known. As shown in Figure 41.6, there are many factors operating both to increase and to decrease sodium excretion, and exactly how the normal balance of net retention is achieved remains a mystery.…”
Section: Volume Regulationmentioning
confidence: 99%